Tapering for competition - Crowther, G. (2000)
The topic is tapering, i.e., reducing one's training load in preparation for an important end-of-season race. Author takes into account and refers to the "best-designed" studies. Key points: - Mileage: less is more - Training intensity: more is more (An emphasis on high-quality workouts and extremely low mileage should help one to fulfill ones potential.) (This article originally appeared in the April 2000 issue of Northwest Runnermagazine.)